Institutional ensuring of the industrial and innovative development of member states of the Eurasian economic union - Khussainova , Zh.S. (BUKETOV BUSINESS REVIEW, 2017)
In article are considered the current state and problems of industrial and innovative development of member countries of the Eurasian economic union, and also a possibility of his activization through development of institutional ensuring of the industrial cooperation in the scientific and technical and innovative and production sphere. In article is noted that one of the main reasons for lag of the industry of member states of EEU in labor productivity on gross value added from the level of economically developed countries, is the imperfect technological structure of an industrial complex that leads to decrease in his competitiveness. It demands combination of efforts of member countries of the Eurasian economic union on reduction of technological lag and to development of export of in common made production on the markets of the third countries. In article is emphasized that activization of industrial cooperation in the scientific and technical, innovative and production sphere of member states of EEU has to be promoted by creation and functioning of the following supranational institutes of development: Euroasian network of industrial cooperation and subcontracting, Euroasian technological platforms, Euroasian engineering center, Euroasian network of a transfer of technologies, uniform digital space of the industry of EEU.